LEARNING OF PETANQUE SPORT TO IMPROVE CONCENTRATION AND ACHIEVEMENT OF STUDENTS IN CENTRAL JAVA (International Conference on Elementary Education, 2018)
The purposes of this research are to study, 1) Overall Petanque Sport, 2) Learning Petanque Sport, 3) Benefits of Petanque Sport learning. This research was conducted in FOPI Central Java. This research is a qualitative research that is interpretative, and presented using descriptive approach. We made observations, analyzed documents, and conducted some interviews to collect our data. The results in this research are as follows. 1) Petanque Sport is a new sport from France that is growing rapidly in Central Java. 2) The most effective socialization and learning efforts are conducted in schools. 3) Participating in Petanque Sport can increase student concentration and achievement in Central Java. Based on the result of the research, Petanque Sport is one of sport branches that has been growing fast in Central Java since 2016. Although classified as a new sport, Petanque can be accepted by children in Central Java because the type of game is very fun, easy to learn, minimal of risk and no physical contact. Petanque game is likes traditional games, for example kelereng or gundu. Application of petanque sport learning in school can improve concentration and achievement of students in Central Java because in Petanque sport there are many numbers that are contested.